2019
DOI: 10.1186/s11671-019-2924-z
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effect of 131I-Labeled Anti-VEGFR2 Targeted Mesoporous Silica Nanoparticles in Anaplastic Thyroid Cancer

Abstract: Anaplastic thyroid cancer (ATC) comprises approximately 2% of all thyroid cancers, and its median survival rate remains poor because of its resistance to conventional therapy. Vascular endothelial growth factor receptor (VEGFR)-targeted therapeutics-loaded mesoporous silica nanoparticles represent a major advance for angiogenesis imaging and inhibition in lethal cancers. In the present study, we aimed to assess whether 131I-labeled anti-VEGFR2 targeted mesoporous silica nanoparticles would have antitumor effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Nanomaterials have been widely used in the field of biomedicine, including silica, liposomes, polymers, and gold and iron oxide nanoparticles (4,45). Compared to other silica nanomaterials, MSNs are widely used due to their higher surface area, non-toxic property, improved ductility and permeability, adjustable pore structure, chemically modifiable outer surface, and improved biological compatibility (45,46).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nanomaterials have been widely used in the field of biomedicine, including silica, liposomes, polymers, and gold and iron oxide nanoparticles (4,45). Compared to other silica nanomaterials, MSNs are widely used due to their higher surface area, non-toxic property, improved ductility and permeability, adjustable pore structure, chemically modifiable outer surface, and improved biological compatibility (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of mesoporous silica nanoparticles (MSNs) was performed as previously reported (4,31). Briefly, cetyltrimethyl ammonium bromide (CTAB; Sigma-Aldrich; Merck KGaA) was dissolved in a solution of water (25 ml), ethanol (5 ml), and caustic soda solution (100 µl; 2 M) and heated to 75˚C under vigorous stirring conditions.…”
Section: Synthesis Of Msns and Modificationmentioning
confidence: 99%
See 2 more Smart Citations
“…The same group has also demonstrated delivery of the MSN encapsulating the anti-cancer drug, sunitinib in a significantly higher amount to the U87MG tumor by targeting VEGFR exploiting VEGF 121 ligand in comparison with the non-targeted delivery [ 119 ]. Moreover, Zhang et al have shown increased targeting ability and retention time of anti-VEGFR2 targeted MSN in anaplastic thyroid cancer tumor-bearing mouse [ 120 ]. Bevacizumab or related antibodies have been also exploited for targeting VEGF receptors.…”
Section: Surface Modification Of Msn For Passive and Active Targetmentioning
confidence: 99%